Epigenetic regulation of mitochondrial function in neurodegenerative disease: New insights from advances in genomic technologies. (20th June 2016) - Devall, Matthew; Roubroeks, Janou; Mill, Jonathan; Weedon, Michael; Lunnon, Katie
Highlights: Variation in nuclear DNA methylation has been associated with neuropsychiatric and neurodegenerative diseases. The mitochondrial genome has been shown to be subject to regulation by DNA methylation. A potential role for alterations in mitochondrial DNA methylation in brain disorders has not yet been investigated. Next generation sequencing allows for an interrogation of the mitochondrial epigenome at single base resolution. Abstract: The field of mitochondrial epigenetics has received increased attention in recent years and changes in mitochondrial DNA (mtDNA) methylation has been implicated in a number of diseases, including neurodegenerative diseases such as amyotrophic lateral sclerosis. However, current publications have been limited by the use of global or targeted methods of measuring DNA methylation. In this review, we discuss current findings in mitochondrial epigenetics as well as its potential role as a regulator of mitochondria within the brain. Finally, we summarize the current technologies best suited to capturing mtDNA methylation, and how a move towards whole epigenome sequencing of mtDNA may help to advance our current understanding of the field.